Elements of style : designing a home & a life - Gates, Erin T. (Simon & Schuster, 2014)
"From the star blogger and designer Erin Gates [comes an] interior design book that shows how designing a home is also a method of personal expression and self-discovery. Drawing on her 10 years of experience running her own design firm, Erin combines practical, honest design advice and ... professional photographs and illustrations with personal essays about lessons she has learned while designing her own home and her own life--the first being: none of our homes or lives are perfect"--